2021
DOI: 10.1007/s00259-020-05166-2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular sources of TSPO expression in healthy and diseased brain

Abstract: The 18 kDa translocator protein (TSPO) is a highly conserved protein located in the outer mitochondrial membrane. TSPO binding, as measured with positron emission tomography (PET), is considered an in vivo marker of neuroinflammation. Indeed, TSPO expression is altered in neurodegenerative, neuroinflammatory, and neuropsychiatric diseases. In PET studies, the TSPO signal is often viewed as a marker of microglial cell activity. However, there is little evidence in support of a microglia-specific TSPO expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
132
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 185 publications
(257 reference statements)
1
132
0
Order By: Relevance
“…However, recent clinical study with [ 11 C]ER176 ( 105 ) and [ 11 C]GE-180 ( 88 ) demonstrated a significant decrease in ligand retention in low-affinity binders, suggesting the necessity of further in vivo examination. Second, the heterogenous cellular sources of TSPO PET tracers have been demonstrated in astrocytes, endothelial cells, and vascular smooth muscle cells, in addition to microglia in both patients with AD and animal models ( 61 , 85 , 86 , 193 , 226 229 ) ( Figures 1A, B ) . Although conventional opinions consider microglia as major cellular source of TSPO in the central nervous system, latest study finds vascular TSPO provides major binding sites for TSPO ligands including most widely used [ 11 C]PK11195 and [ 11 C]PBR28 in normal mouse brains ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent clinical study with [ 11 C]ER176 ( 105 ) and [ 11 C]GE-180 ( 88 ) demonstrated a significant decrease in ligand retention in low-affinity binders, suggesting the necessity of further in vivo examination. Second, the heterogenous cellular sources of TSPO PET tracers have been demonstrated in astrocytes, endothelial cells, and vascular smooth muscle cells, in addition to microglia in both patients with AD and animal models ( 61 , 85 , 86 , 193 , 226 229 ) ( Figures 1A, B ) . Although conventional opinions consider microglia as major cellular source of TSPO in the central nervous system, latest study finds vascular TSPO provides major binding sites for TSPO ligands including most widely used [ 11 C]PK11195 and [ 11 C]PBR28 in normal mouse brains ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, knowledge on levels and cellular localization of TSPO expression in healthy and diseased human brain largely stems from post-mortem studies using TSPO radioligands, but results are highly inconsistent [59,60]. Cellular sources of TSPO expression in healthy and diseased brain have recently been reviewed by Nutma et al [61]. In short, immunohistochemical studies for TSPO in healthy human brain revealed that TSPO is expressed in glial cells (microglia and astrocytes), oligodendrocytes and vascular endothelial cells [62,63].…”
Section: Translocator Protein 18 Kda (Tspo) -Gold Standard For Pet Imaging Of Activated Microgliamentioning
confidence: 99%
“…to nutritional change TSPO expression in the brain changes drastically in response to disease [30], potentially through a CpG methylation-mediated epigenetic mechanism [138]. It is therefore not surprising that TSPO expression is also sensitive to alterations in diet.…”
Section: Brain Tspo Neuroplasticity In Responsementioning
confidence: 99%